Sandwich-like sound-driven triboelectric nanogenerator for energy harvesting and electrochromic based on Cu foam - Qiu, Wenzheng; Feng, Yange; Luo, Ning; Chen, Shougang; Wang, Daoai (Nano energy, 2020)
As a kind of environmental dissipative energy, acoustic energy is common but difficult to collect and utilize effectively owing to its low energy density and special acoustic state. In this work, a new type of triboelectric nanogenerator (TENG) based on porous foam copper with sandwich-like friction pairs is designed to harvest sound energy efficiently from the environment. The sound-driven TENG is mainly composed of Cu foam, polyvinylidene fluoride (PVDF) nanofibers and nylon fabric, in which the Cu foam is used as a sound collector, conductor and amplifier, as well as the friction layer and conductive layer of the TENG. The thin and light PVDF nanofiber membrane and nylon fabric are used as vibration membranes, which are easy to generate vibration under weak sound to harvest the sound energy under wideband frequencies. This sound-driven TENG shows high triboelectric output performance with a maximum current density up to 25.01 mA/m2 and a charging rate of 20.91 μC/s with a charging transformation efficiency up to 59.85%, which can light up 384 LEDs and drive an electrochromic device for reversible color changing. Importantly, the sound-driven TENG has good working stability. It can work continuously for 7 days under loudspeaker driving without decay. This type of sound-driven TENG has potential application in the field of audio frequency analysis, noise detection, energy supply and presents promising potential to be a self-powered system in the electrochemical industry. A new kind of sandwich-like sound-driven TENG based on porous network structured Cu foam and flexible electrospun polyvinylidene fluoride (PVDF) nanofiber and nylon fabric is constructed for acoustic energy harvesting. The purpose of this work is to make use of sound wave energy with broad driving frequency on the basis of TENG technology, and make up for its weak force through reasonable device structure design, so as to realize the effective collection and utilization of sound wave energy in our living environment. [Display omitted] •A sandwich-like sound-driven TENG based on Cu foam is fabricated to absorb acoustic energy into triboelectricity.•The TENG is composed of 3 layers with dual friction pairs, thus its output current density reaches up to 25.01 mA/m2.•An electrochromic device is designed and shows promising potential as a self-powered system in electrochemical industry.